2021
DOI: 10.1021/acs.orglett.1c03955
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Difunctionalization of Terminal Alkynes: Access to 1,4-Dicarbonyl Compounds

Abstract: 1,4-Dicarbonyl compounds are versatile scaffolds for the heterocycle synthesis, including the Paal–Knorr reaction. Herein, a feasible electrosynthesis method to access 1,4-dicarbonyl compounds has been developed from simple alkynes and 1,3-dicarbonyl compounds. When the undivided cell is combined with the constant current mode, aryl alkynes containing numerous medicinal motifs with 1,3-dicarbonyl esters or ketones react smoothly. External oxidant and catalyst-free conditions conform to the requirements of gree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…On the other hand, hydrogen atom trans- The direct electrochemical difunctionalization of terminal alkynes with 1,3-dicarbonyl esters or ketones to synthesize 1,4dicarbonyl compounds was reported by Lei and co-workers in 2021 (Scheme 21). 49 The reaction is achieved at 60 °C in a solution of K 2 CO 3 in AcOH/DCE. The radical addition of 21-8 produced by the anodic oxidation of 21-1 to terminal alkynes 21-2 furnished alkenyl radical intermediates 21-9, which are further oxidized by the anode and trapped by H 2 O produced by the reaction of K 2 CO 3 and AcOH to afford products 21-3.…”
Section: Addition Of 13-dicarbonyl Radicals To Alkynesmentioning
confidence: 99%
“…On the other hand, hydrogen atom trans- The direct electrochemical difunctionalization of terminal alkynes with 1,3-dicarbonyl esters or ketones to synthesize 1,4dicarbonyl compounds was reported by Lei and co-workers in 2021 (Scheme 21). 49 The reaction is achieved at 60 °C in a solution of K 2 CO 3 in AcOH/DCE. The radical addition of 21-8 produced by the anodic oxidation of 21-1 to terminal alkynes 21-2 furnished alkenyl radical intermediates 21-9, which are further oxidized by the anode and trapped by H 2 O produced by the reaction of K 2 CO 3 and AcOH to afford products 21-3.…”
Section: Addition Of 13-dicarbonyl Radicals To Alkynesmentioning
confidence: 99%
“…Several studies have reported the construction of C−C bonds by direct electrolysis [17–19] . Meanwhile, indirect electrolysis is also a significant tool for C−C bond formation [20–25] . Halides such as bromides and iodides can be oxidized to active cationic species on the anode enabling useful chemical reactions.…”
Section: Electrochemical Reactions Using Halogen Mediatorsmentioning
confidence: 99%
“…On the basis of these mechanistic probe experiments and previously relevant literature, ,, we propose our speculation on the [3 + 2] annulation process (Figure , D). Anodic oxidation of Fc produced Fc + species, which with the assistance of NaOAc oxidized the β-keto compound to carbon-centered radical 61 and regenerated the Fc catalyst.…”
mentioning
confidence: 94%
“…Particularly, monosubstituted ethynylbenzenes bearing electron-donating groups such as alkyl, alkoxyl, and phenyl afforded the corresponding products in satisfactory yields regardless of the substitution positions (4−14). Moreover, ester (15), boronate (16), and free amine (21) were also compatible with the established method. Electronwithdrawing halogen and cyno were also investigated and proven to be well tolerated functionalities to give the cyclization products 17−20, albeit with inferior results.…”
mentioning
confidence: 99%